Integration of Virtual Reality and Digital Game-Based Learning in Education: Accelerating English Language Communication - Pratiwi, Alifiah; Reskiawan, Bimas; Suryadi, Ray; Andas, Netty Huzniati; Hendrawan, Kevin (Universitas Islam Negeri Palopo, 2025)
This study was initiated in response to the challenges faced by students who are not accustomed to practicing English speaking due to a lack of self-confidence and heightened anxiety when communicating with others or with native speakers. To address these issues, the study explores the potential of Virtual Reality (VR) technology to foster the development of students’ English communication skills within an autonomous, interactive, and engaging environment. Such an environment is expected to increase students’ learning motivation while simultaneously improving the overall quality of instruction. The primary aim of this research is to contribute to the body of knowledge by developing a prototype of a digital platform termed Metaversity, defined as a virtual learning environment that integrates the immersive features of the Metaverse ecosystem with the pedagogical foundations of Digital Game-Based Learning (DGBL). The participants of the study consisted of 30 undergraduate students from Universitas Sembilanbelas November Kolaka. Employing a Research and Development (R&D) approach, the study adopted the ADDIE model, which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. The resulting learning media integrates VR, DGBL, and communication platforms such as VRChat and Discord into a cohesive system. Validation by media experts yielded an average score of 4.35 out of 5, which falls into the “highly feasible” category. Meanwhile, students’ responses reached an average of 82.5%, placing the product within the “good–very good” range. The findings provide compelling evidence that the developed medium is effective in enhancing students’ motivation, self-confidence, and English-speaking competence. Furthermore, the integration of VR and DGBL fosters active engagement, alleviates language anxiety, and creates an immersive and enjoyable learning experience. These outcomes highlight the potential of Metaversity-based platforms as innovative solutions in higher education language learning contexts.